RENTABILITAS USAHA BAWANG GORENG PADA CV. DUTA AGRO LESTARI DI KOTA PALU - Nanong, Marlina; Mappatoba, Marhawati; Howara, Dafina (AGROTEKBIS, 2017)
Agricultural development in Central Sulawesi is directed to increase the production and income of farmers. One main stay commodity that can increase the income of farmers is a valley commodity onion Palu. The fried onion industry has enough potential to be developed, in addition to extending the use fulness of valley red onion Palu also able to increase household income. Research this aims for knowing magnitude income and profitability business that obtainable business fried onion CV. Agro Lestari City Palu. Determination locations research selected in deliberate (purposive), with consideration that fried onion this constitute false one center business with capacity productionÂ fried onion the most in City Palu that is 57,600 kg per year. Respondents in this research that led the company and two employees. Data that in gather is data primary and data secondary. The analysis method is the analysis of revenue ( Â = TR - TC) and profitability analysis. The results showed the presence of additional capital of as big asÂ IDR. 100.000.000 with an interest rate of 18% per year, the business crown fried onions obtainan average value of 35.45% economic profitability, while the value of equity earnings yield an average value of 34.26%. Key Words : Profitability, business, Fried Onions, Palu.